2017
DOI: 10.1097/brs.0000000000001856
|View full text |Cite
|
Sign up to set email alerts
|

Static Compression Induces ECM Remodeling and Integrin α2β1 Expression and Signaling in a Rat Tail Caudal Intervertebral Disc Degeneration Model

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…Although one study found that physiological level of dynamic compression induced integrin α5β1 expression in rat disc explants 187 , other studies find that degenerative static compressive loading in vivo upregulate β1 expression in NP cells, and activates downstream signaling 188 .…”
Section: Cell-ecm Interactionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although one study found that physiological level of dynamic compression induced integrin α5β1 expression in rat disc explants 187 , other studies find that degenerative static compressive loading in vivo upregulate β1 expression in NP cells, and activates downstream signaling 188 .…”
Section: Cell-ecm Interactionsmentioning
confidence: 98%
“…Although one study found that physiological level of dynamic compression induced integrin α5β1 expression in rat disc explants, other studies find that degenerative static compressive loading in vivo upregulate β1 expression in NP cells, and activates downstream signaling. Moreover, disruption of β1 integrin signaling may underlie disc cell apoptosis induced by mechanical stress in disc degeneration models.…”
Section: Response To Abnormal Mechanobiology and Degenerationmentioning
confidence: 99%
“…Previous studies found an increase in NP cell apoptosis and a decrease in NP matrix production as a result of overloaded mechanical compression [9, 10]. Similarly, several studies have demonstrated that mechanical stimulation plays an important role in regulating disc biology and have indicated that mechanical overloading is a risk factor for disc degeneration [11, 12]. Therefore, additional studies of the high-magnitude compression-induced pathological alterations of NP cells will contribute to a better understanding of mechanical load-related disc degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the degree of degeneration heavily depends on time and the extent of bending force applied to the rat tail. Another classic model, Ilizarov-type compressive model, was widely used by many researchers due to its reliable installation and satisfactory modeling results [11,[22][23][24]. However, a set of springs were mainly used in these studies as the provider of compression loads.…”
Section: Discussionmentioning
confidence: 99%